2022
DOI: 10.1155/2022/4640161
|View full text |Cite
|
Sign up to set email alerts
|

Role of ER Stress in Xenobiotic-Induced Liver Diseases and Hepatotoxicity

Abstract: The liver is a highly metabolic organ and plays a crucial role in the transportation, storage, and/or detoxication of xenobiotics. Liver damage induced by xenobiotics (e.g., heavy metal, endocrine disrupting chemicals, Chinese herbal medicine, or nanoparticles) has become a pivotal reason for liver diseases, leading to great clinical challenge and much attention for the past decades. Given that endoplasmic reticulum (ER) is the prominent organelle involved in hepatic metabolism, ER dysfunction, namely, ER stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 94 publications
(111 reference statements)
0
3
0
Order By: Relevance
“…We used gene ontology analysis to demonstrate that the unfolded protein response (UPR) was enriched in the upregulated GES for IILI. UPR is tightly linked to ER stress associated with IILI [ 32 , 33 ]. Previous zebrafish studies demonstrated that 4-phenylbutyrate, an ER stress inhibitor, ameliorates liver injury induced by INH and lipopolysaccharides [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…We used gene ontology analysis to demonstrate that the unfolded protein response (UPR) was enriched in the upregulated GES for IILI. UPR is tightly linked to ER stress associated with IILI [ 32 , 33 ]. Previous zebrafish studies demonstrated that 4-phenylbutyrate, an ER stress inhibitor, ameliorates liver injury induced by INH and lipopolysaccharides [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“… 1 The ER plays a crucial role in protein quality control and supporting cellular activities. 2 , 3 Disruption of ER homeostasis due to physiological or pathological stimuli leads to the accumulation of misfolded and unfolded proteins, initiating endoplasm ic reticulum stress (ERS) and triggering the unfolded protein response (UPR). 4 In the short term, the UPR serves as an adaptive response, enhancing the cell's capacity to handle ERS and restore ER homeostasis through protein processing, thereby promoting cell survival.…”
Section: Introductionmentioning
confidence: 99%
“…487 [19]. The liver is a target of xenobiotic toxicity, and is the principal site for their metabolism [20,21]. The HepaRG cell line represents an interesting metabolically competent in vitro model to investigate the hepatotoxicity of xenobiotic compounds [22].…”
Section: Introductionmentioning
confidence: 99%